Cardiac screening: time to move forward! - Borjesson, M.; Drezner, J. (British Journal of Sports Medicine, 2012)
Cardiac screening of athletes has been passionately discussed for over two decades. Increased attention and controversy emerged after the publication of the 2005 European Society of Cardiology (ESC) guidelines endorsing a screening protocol inclusive of a resting 12-lead ECG. The American Heart Association (AHA) also strongly advocates for cardiovascular screening in athletes, but recommends a programme based only on a personal and family history and physical examination. After years of fervent debate, it is time to put passion aside and instead focus on the expanding body of knowledge which now exists. With careful analysis and thoughtful perspective, the discussion on cardiac screening can move forward—beyond the usual rhetoric—to benefit athletes and prevent sudden death.